New patterns for comparative religion : passages to an evolutionary perspective - Paden, William E. (Scientific studies of religion (Bloomsbury (Firm)), 2016)
"The cross-cultural study of religion has always gone hand in hand with the worldview, sciences, or intellectual frameworks of the time. These frames, whether focused on psychology or politics, gender or colonialism, bring out perspectives for understanding religious behavior. Today one of our common civic worldviews is represented in the shift from scriptural to evolutionary history. This volume brings together in one place key essays by professor emeritus William Paden, showing a progression of steps he has taken in exploring bridgeworks between comparative religion and evolutionary models of religious behavior. One of the leading scholars in religious studies, Paden shows ways that religion can be contextualized as part of the natural world and thus seen as reflecting the ingrained sociality and world-making drive of the human species. Paden argues that although comparativism has been challenged as too culture-bound, too western, or too gendered, cross-over categories and concepts between religious traditions cannot be avoided. Arguing that there are recurrent patterns of human behavior common to our species and that thereby underlie all cultures, he proposes that the missing link in the Religion Evolution debate is comparative religion, a global, cross-cultural perspective on religious behaviours throughout time. Each article is contextualized within this overall trajectory of thought within Paden's work and the history of the discipline as a whole."--Bloomsbury Publishing.